Le Corbusier e la villa Savoye: un caso di restauro autoriale / Le Corbusier and the villa Savoye: a case of authorial restoration - Caccia Gherardini, Susanna (Saggi. Architettura, Pianificazione, Paesaggio, Design, 2023)
Following the investigative paths, the author interlaces a series of documents and clues to delineate the events of the restoration of the Villa Savoye by Le Corbusier, but above all the role played by the various actors involved in this story, which is still not closed. From George Everard Kidder Smith to the multifaceted Jean-Louis Véret, who would in fact become the villa's most stubborn conservator and interpreter, starting with the writing of his Carnet d'identité, one of the most ambiguous and fascinating sources for the history of the restoration of modern architecture. Susanna Caccia Gherardini, thanks to her research time as Guest Scholar at the Getty Conservation Institute in Los Angeles, thus adds a new piece to the studies she has already published on the subject.